Surface Integrity Characteristics of NiTiHf High Temperature Shape Memory Alloys - KAYNAK, YUSUF (SPRINGER-VERLAG SINGAPORE PTE LTD, 2020)
This present study focuses on the surface integrity characteristics of the machined NiTiHf high temperature shape memory alloys. The NiTiHf specimens were machined under dry, minimum quantity lubrication (MQL) and cryogenic cooling at two different cutting speeds. Experimental data on microhardness, latent heat and phase transformation temperature is presented and analyzed to evaluate the surface and subsurface characteristics of the machined NiTiHf specimens. It is found that machining process particularly cryogenic machining alters microhardness, latent heat and phase transformation temperature of Ni-rich NiTiHf alloy. This study demonstrates that cryogenic machining process leads to occurring strain hardened layer on the surface and subsurface of machined workpiece. Phase transformation response including transformation temperature and latent heat for transformation of this affected layer shows significant difference comparing with the bulk of the workpiece. This difference is evidently observed from the cryogenically machined specimens than the specimens machined under dry and MQL conditions.
Keywords: Surface integrity; High temperature shape memory alloys; Machining; Phase transformation; TRANSFORMATION BEHAVIOR